STUDI TEKNIS PLTS ROOFTOP 3KWP FRAMELESS WITH ON-GRID SYSTEM DI LINGKUNGAN KORI NUANSA JIMBARAN - I G.N.A.B Rama Wahyu Dewangga; Ida Ayu Dwi Giriantari; I Wayan Sukerayasa (Program Studi Teknik Elektro UNUD, 2021)
Solar light is an environmentally friendly renewable energy. According to RUEN, BaliProvince has a fairly large potential for solar light utilization, namely 1,254 MW with a target forPLTS development in 2025 of 8.62% or 108.2 MW of its total potential. Therefore, this researchfocuses on the utilization of PLTS Rooftop on-grid as an energy supply at Kori NuansaJimbaran's residence which explains the specifications of the installed PLTS materials andcomponents, as well as the design of the PLTSinstallation in Rooftop terms of technical termsaccording to the requirements of PT. PLN (Persero). The method used is literature review,observation, data collection, data analysis and conclusions. The results showed that the totaldaily load calculation was 26,151 W/day and the total daily energy that could be generated fromthe calculation was 14.58 kWh/day with the measurement results at the research location of13.4 kWh/day where there was a difference of 1.18 kWh caused by due to losses in the system.When viewed from the total daily load the PLTS system has not met the needs, but functionallythe PLTS system is intended for daytime loads so that the needs are appropriate. Optimalinclination angle of 14.66calculation results areº however on measurementsusing a protractortool obtained18º this because the angle of inclination of the solar panels follows the direction ofthe slope of the roof. The installed PLTS design has met the standards of the Minister of Energyand Mineral Resources No. 49 of 2018 and has received an Operational Worthiness Certificate(SLO) from PT. PLN (Persero).